Proceedings of the 21st International Electronic Conference on Synthetic Organic Chemistry 2017
DOI: 10.3390/ecsoc-21-04781
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study of the Decomposition Pathways of 5,5'-bitetrazole-1,1'-diide as a Parent Anion in the Family of Highly Energetic Green Explosives

Abstract: Abstract:The decomposition pathways of the anionic parts of the 5,5'-bitetrazole-related energetic salts are studied theoretically using highly-symmetric 5,5'-bitetrazole-1,1'-diide (point group D2d) as a model compound. The relaxed scans for all the four symmetry unique bonds elongation have been performed at the wB97XD/6-311+G(d,p) level of theory. The results have revealed that the most preferable decomposition route is the C5-N1 bond elongation. Breaking of the bonds has been tracked using the QTAIM analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…A few studies have only concomitantly mentioned the variation of aromaticity in studying other problems but no further step. [107,108] Owing to the close relationship between aromaticity and stability, we employ two complexes as shown in Figure 1, where complex I is the most common molecular structure corresponding to the crystal structure of TKX-50 [109][110][111] and complex II is the most stable one in ten possible complexes obtained by Talawar et al [112] through complex searching at ωb97xd/6-311 + + g-(3df,3pd) level of theory in the gas phase, to deep study the aromaticity of TKX-50 molecules and first found that the aromaticity of TKX-50 is constituted by π-aromaticity and a comparable amount of σ-aromaticity. This provides a new and deeper perspective on the aromaticity of TKX-50 and its related properties as a promising energetic material such as stability, impact sensitivity, and heat decomposition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have only concomitantly mentioned the variation of aromaticity in studying other problems but no further step. [107,108] Owing to the close relationship between aromaticity and stability, we employ two complexes as shown in Figure 1, where complex I is the most common molecular structure corresponding to the crystal structure of TKX-50 [109][110][111] and complex II is the most stable one in ten possible complexes obtained by Talawar et al [112] through complex searching at ωb97xd/6-311 + + g-(3df,3pd) level of theory in the gas phase, to deep study the aromaticity of TKX-50 molecules and first found that the aromaticity of TKX-50 is constituted by π-aromaticity and a comparable amount of σ-aromaticity. This provides a new and deeper perspective on the aromaticity of TKX-50 and its related properties as a promising energetic material such as stability, impact sensitivity, and heat decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…However, the aromaticity of the bi‐tetrazole ring in TKX‐50 has not attracted much attention from researchers. A few studies have only concomitantly mentioned the variation of aromaticity in studying other problems but no further step [107,108] . Owing to the close relationship between aromaticity and stability, we employ two complexes as shown in Figure 1, where complex I is the most common molecular structure corresponding to the crystal structure of TKX‐50 [109–111] and complex II is the most stable one in ten possible complexes obtained by Talawar et al [112] .…”
Section: Introductionmentioning
confidence: 99%